PENGARUH RUANG FISKAL, PENDAPATAN ASLI DAERAH, DANA ALOKASI UMUM, PERSENTASE PENDUDUK MISKIN, DAN RATA-RATA LAMA SEKOLAH TERHADAP BELANJA PENDIDIKAN - Hidayati, Nur Rohmah; Bawono, Andy Dwi Bayu (Sekolah Tinggi Ilmu Ekonomi Bank BPD Jawa Tengah, 2020)
This research aims to examine the influence of Fiscal Space, Locally Generated Revenue(PAD), General Allocation Funds(DAU), Poverty Rate (PPM), and Mean Years School(RLS) on Education Expenditures. The population used in this study is all regency/city in Indonesia. The sampling method in this research using purposive sampling method, collected data processed 505 regency/city samples. The analysis used in this research is multiple linear regression analysis processed using the Statistical Package for Social Science (SPSS) version 21.00 software program. The simulant test result shows that Fiscal Space, Locally Generated Revenue (PAD), General Allocation Fund (DAU), Poverty Rate (PPM), and Mean Years School(RLS) significantly influence Education Expenditures. While the partial test shows that Fiscal Space, Local Original Revenue (PAD), General Allocation Fund (DAU) effect on Education Expenditures, Proverty Rate (PPM) has no effect on Education Expenditures, and Mean Years School (RLS) negatively influences Education Expenditures